Probing the Reactivity of 2,4-Dichlorofuro[3,4-d]pyrimidin-7-one: A Versatile and Underexploited Scaffold to Generate Substituted or Fused Pyrimidine Derivatives - Vincetti, Paolo; Costantino, Gabriele; Martina, Maria Grazia; Radi, Marco (Synlett, 2019)
Herein, we describe the results of our investigation on the chemical reactivity and versatility of a poorly explored scaffold: 2,4-dichlorofuro[3,4-d]pyrimidin-7-one (3). Highly functionalized pyrimidines can be obtained with a divergent approach by reacting the key intermediate 3 with different amine nucleophiles under carefully controlled reaction conditions. The set-up of a microwave-assisted one-pot, two- or three-step protocol to rapidly generate 2,4,5,6-tetrasubstituted or fused pyrimidines is also reported.
Keywords: orotic acid; pyrimidines; multicomponent reactions; microwave